Manu, Vasu caritrala tulanātmaka pariśīlanamu - Sujātāreḍḍi, Mudigaṇṭi (s.n., 1981)
Comparative study of the 16th century Telugu poetical works, Manucaritramu by Allasāni Peddana and Vasucaritra by Rāmarāja Bhūshaṇa.